Determinants of sexting behavior among emerging adults in Malaysia - Lee, Li Teng; Ong, Pei Ling; Wong, Yoke Ting (2022)
Researchers have paid close attention to sexting behaviour in recent years, as various detrimental outcomes have been highlighted, such as risky sex, reputation damage, and cyberbullying. Previous research was primarily focused on young adults, and thus there are limited studies on emerging adults. Other than that, sexting research is still in its infancy, particularly in the Malaysian context. The present study employed quantitative, cross-sectional, and correlational research designs to better understand sexting behaviour and its associated factors among emerging adults, as well as the gender and relationship status disparities in sexting behaviour. As a result, a total of 197 participants (M = 22.76, SD = 2.20) who engaged in sexting behaviour participated in this research using the purposive sampling method. Contrary to the hypothesis of this study, the results showed that male emerging adults have higher engagement in sexting behaviour than females. All the variables were significantly correlated to sexting at the bivariate level. However, the controlled effect of age, gender, and relationship status in hierarchical linear regression revealed that only sexual intention was correlated to sexting behaviour. Therefore, the findings of this study might contribute to enriching the existing literature on sexting behaviours, and some practical implications were discussed.